2018
DOI: 10.1097/sap.0000000000001284
|View full text |Cite
|
Sign up to set email alerts
|

How Big is Too Big

Abstract: We found obese women to have a higher rate of abdominal donor site complications; however, this risk seems to level off at class I or II obesity. We have modified our surgical technique of managing the abdominal donor site to optimize our outcomes in the morbidly obese patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
1
7
1
Order By: Relevance
“…30 Similarly, Spitz et al found donor site complication rates to be equivalent between obesity classes II and III, with more of a difference between classes II and I. 44 Although these findings contrasted from ours, it is important to reiterate that our sample uniquely focused on DIEP flaps exclusively.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…30 Similarly, Spitz et al found donor site complication rates to be equivalent between obesity classes II and III, with more of a difference between classes II and I. 44 Although these findings contrasted from ours, it is important to reiterate that our sample uniquely focused on DIEP flaps exclusively.…”
Section: Discussioncontrasting
confidence: 63%
“…The benefits of CTA imaging are well-documented: the knowledge of perforator course and caliber allows the surgeon to optimize flap design, mitigate dissection difficulty, and theoretically reduce operative time. 44 61 62 63 64 Routine use also ensures that all patients can be evaluated for preexisting abdominal scarring, flap thickness, and alternative options such as the superficial inferior epigastric system. There is evidence that the radiolucency of subcutaneous tissue may make cutaneous perforators easier to visualize in obese patients relative to leaner patients.…”
Section: Discussionmentioning
confidence: 99%
“…The authors did find that a higher Adult Comorbidity Evaluation score was associated with worse outcomes, and obesity is factored into the calculation of the score. In contrast, obesity has been identified as a strong risk factor for complications in microvascular reconstruction of other anatomical regions, such as the breast 26,27 . Spitz et al 26 reported an increased risk of donor and recipient site complications in obese women undergoing autologous breast reconstruction in comparison to women with lower BMI, but differences within classes of obesity were less pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, obesity has been identified as a strong risk factor for complications in microvascular reconstruction of other anatomical regions, such as the breast 26,27 . Spitz et al 26 reported an increased risk of donor and recipient site complications in obese women undergoing autologous breast reconstruction in comparison to women with lower BMI, but differences within classes of obesity were less pronounced. However, in a large cohort of 1258 patients undergoing breast reconstruction, class III (morbid) obesity was found to be associated with worse outcomes, including both major and minor complications, than lower classes of obesity 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In Sweden, active smoking is a contraindication for DIEP flap reconstruction since it is significantly associated with impaired wound healing, infection and postoperative complications such as flap loss, hematoma or fat necrosis [44][45][46]. Also a high BMI is a contraindication for DIEP flap reconstruction, since patients with a BMI >30 kg/m 2 are more likely to experience surgical as well as medical postoperative complications [47][48][49]. Swedish recommendations state that patients undergoing DIEP should have a BMI <30 kg/m 2 , quit smoking at least four weeks before surgery and be free of cancer relapse [2].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%